2007
DOI: 10.1002/pola.21984
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of poly(ester amide)s by the melt polycondensation of semiaromatic polyesters with ethanolamine and their characterization

Abstract: Semiaromatic poly(ester amide)s (PEAs) were synthesized by the melt polycondensation of ethanolamine (EA) derivatives with dimethyl terephthalate and ethylene glycol in the presence of tetrabutyl titanate as a catalyst, and their crystallization and thermal properties were investigated. The introduction of an amide group into a semiaromatic polyester such as poly(ethylene terephthalate) (PET) produced PEAs (EA-modified PET polymers) with an increase in the melting point. However, these PEAs were found to decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…Poly(ester amide)s (PEAs) have been proposed as a class of materials having the potential to exhibit optimal properties for a diverse range of biomedical applications 19. By definition they comprise both ester and amide linkages in their backbones, and several different classes of backbones have been proposed 20–27. The PEAs of interest in the present work are those comprising diols, diacids, and α‐amino acids as illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(ester amide)s (PEAs) have been proposed as a class of materials having the potential to exhibit optimal properties for a diverse range of biomedical applications 19. By definition they comprise both ester and amide linkages in their backbones, and several different classes of backbones have been proposed 20–27. The PEAs of interest in the present work are those comprising diols, diacids, and α‐amino acids as illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The same MS method was used to investigate the effect of long time aging on the chain end of poly( p -methoxystyrene) . Furthermore, the characterization of poly(ether imide)s , , poly(amidoamines), poly(ester amide)s , poly(epichlohydrin) , telechelic poly( N -isopropylacrylamides) , cyclic poly(lactides) , enantiomeric poly(α-methyl-α-ethyl-β-propiolactones) , and multicyclic poly(ether sulfone)s by MALDI-TOF MS was reported. Liu and Mishra described the atom-transfer radical polymerization of menthyl acrylate .…”
Section: Polymer Synthesismentioning
confidence: 99%
“…Harashina at al. 32 studied the thermal decomposition of ethanolaminemodified PET and [poly(ester amide)] and found that the modified poly(ester amide) was less stable than PET. They proposed a decomposition method to demonstrate this phenomenon.…”
Section: Tga Of Prepba Extpba Prepbs and Extpbsmentioning
confidence: 99%